2014
DOI: 10.2215/cjn.10261013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Associations of Muscle Mass and Muscle Strength with Mortality in Dialysis Patients

Abstract: Background and objectives Reduced muscle mass and strength are prevalent conditions in dialysis patients. However, muscle strength and muscle mass are not congruent; muscle strength can diminish even though muscle mass is maintained or increased. This study addresses phenotype and mortality associations of these muscle dysfunction entities alone or in combination (i.e., concurrent loss of muscle mass and strength/mobility, here defined as sarcopenia).Design, setting, participants, & measurements This study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
368
7
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(411 citation statements)
references
References 43 publications
21
368
7
15
Order By: Relevance
“…Only two studies used more objective assessment of physical performance by measuring HGS (41,42). In 330 patients, lower HGS (,20 kg in women and ,30 kg in men) at dialysis initiation was found to be significantly associated with a higher mortality risk compared with those with appropriate HGS (adjusted HR, 1.79; 95% CI, 1.09 to 2.94) (41).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Only two studies used more objective assessment of physical performance by measuring HGS (41,42). In 330 patients, lower HGS (,20 kg in women and ,30 kg in men) at dialysis initiation was found to be significantly associated with a higher mortality risk compared with those with appropriate HGS (adjusted HR, 1.79; 95% CI, 1.09 to 2.94) (41).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Observational studies have shown an inverse correlation between muscle mass and blood levels of IL‐6 and C reactive protein in CKD patients,12, 107, 108 postulating inflammation as an additional cause of muscle wasting in this population 109, 110, 111. Although the process by which inflammation produces sarcopenia has not yet been identified, several mechanisms have been described, including activation of NF‐κβ and angiotensin II pathways,112, 113, 114 and the ATP‐dependent ubiquitin–proteasome system, which has been identified as the most important pathway for muscle wasting 115.…”
Section: Bone and Musculoskeletal Abnormalities In Chronic Kidney Dismentioning
confidence: 99%
“…These observations collectively imply an integrated role of vitamin D for bone and muscle health. Such a role may have substantial clinical implications, especially for CKD patients, in which musculoskeletal alterations and their complications, including muscle pain and weakness, sarcopenia, fatigability, reduced exercise tolerance, fractures, and falls, adversely affect quality of life and survival 12, 13, 14, 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…With these tests it has been shown that for every 0.1 m/s decrease in gaitspeed, the risk of mortality increases by 26%, while a one-second increase in time-up-and-go test increases mortality by 8% [8]. Physical function and muscle strength do not necessarily depend on muscle mass; some studies have reported that the first one is a better predictor of mortality in patients with CKD [9,10].…”
mentioning
confidence: 99%